Differential Expression of Human MicroRNAs During Dengue Virus Infection in THP-1 Monocytes - Rossi, Átila Duque; Higa, Luiza Mendonça; Herlinger, Alice Laschuk; Ribeiro-Alves, Marcelo; de Menezes, Mariane Talon; Giannini, Ana Lucia Moraes; Cardoso, Cynthia Chester; Da Poian, Andrea T.; Tanuri, Amilcar; Aguiar, Renato Santana (Frontiers in Cellular and Infection Microbiology, 2021)
Dengue virus (DENV) is the most widespread arbovirus, responsible for a wide range of clinical manifestations, varying from self-limited illness to severe hemorrhagic fever. Dengue severity is associated with host intense proinflammatory response and monocytes have been considered one of the key cell types involved in the early steps of DENV infection and immunopathogenesis. To better understand cellular mechanisms involved in monocyte infection by DENV, we analyzed the expression levels of 754 human microRNAs in DENV-infected THP-1 cells, a human monocytic cell line. Eleven human microRNAs showed differential expression after DENV infection and gene ontology and enrichment analysis revealed biological processes potentially affected by these molecules. Five downregulated microRNAs were significantly linked to cellular response to stress, four to cell death/apoptosis, two to innate immune responses and one upregulated to vesicle mediated, TGF-β signaling, phosphatidylinositol mediated signaling, lipid metabolism process and blood coagulation.